Recovering from an acute cardiac event - the relationship between depression and life satisfaction - Page, K.; Davidson, Patricia; Edward, K.; Allen, J.; Cummins, R.; Thompson, D.; Worrall-Carter, L. (Blackwell Publishing, 2010)
Aims. This study sought to measure the rates and trajectory of depression over six months following admission for an acute cardiac event and describe the relationship between depression and life satisfaction. Background. Co-morbid depression has an impact on cardiac mortality and is associated with the significant impairment of quality of life and well-being, impairments in psychosocial function, decreased medication adherence and increased morbidity. Design. This was a descriptive, correlational study. Method. The study was undertaken at a large public hospital in Melbourne. Participants were asked to complete a survey containing the cardiac depression scale (CDS) and the Personal Well-being Index. Results. This study mapped the course of depression over six months of a cohort of patients admitted for an acute cardiac event. Significant levels of depressive symptoms were found, at a level consistent with the literature. A significant correlation between depressive symptoms as measured by the CDS and the Personal Well-being Index was found. Conclusions. Depression remains a significant problem following admission for an acute coronary event. The Personal Wellbeing Index may be a simple, effective and non-confrontational initial screening tool for those at risk of depressive symptoms in this population. Relevance to clinical practice. Despite the known impact of depression on coronary heart disease (CHD), there is limited research describing its trajectory. This study makes a compelling case for the systematic screening for depression in patients with CHD and the importance of the nursing role in identifying at risk individuals.